The effect of the lockdown executive order during the COVID-19 pandemic in recent trauma admissions in Puerto Rico - Pedro E. Ruiz-Medina; Ediel O. Ramos-Meléndez; Kerwin X. Cruz-De La Rosa; Antonio Arrieta-Alicea; Lourdes Guerrios-Rivera; Mariely Nieves-Plaza; Pablo Rodríguez-Ortiz (BMC, 2021)
Abstract Background The COVID-19 pandemic led to world-wide restrictions on social activities to curb the spread of this disease. Very little is known about the impact of these restrictions on trauma centers. Our objective was to determine the effect of the pandemic-associated lockdown on trauma admissions, patient's demographics, mechanisms of injury, injury severity, and outcomes in the Puerto Rico Trauma Hospital. Methods An IRB-approved quasi-experimental study was performed to assess the impact of the restrictions by comparing trauma admissions during the lockdown (March 15, 2020 - June 15, 2020) with a control period (same period in 2017-2019). Comparisons were done using the Pearson's chi-square test, Fisher exact test, or Mann-Whitney U test, as appropriate. A negative binomial model was fitted to estimate the incidence rate ratio for overall admissions among pre-lockdown and during-lockdown periods. Statistical significance was set at p < 0.05. Results A total of 308 subjects were admitted during the quarter of study for 2017; 323, for 2018; 347, for 2019; and 150, for 2020. The median (interquartile range) age of patients rose significantly from 40 (33) years to 49 (30) years (p < 0.001) for the lockdown period compared to the historical period. Almost all mechanisms of injury (i.e., motor vehicle accident, assault, pedestrian, burn, suicide attempt, other) had a slight non-significant reduction in the percentage of patients presenting with an injury. Instead, falls experienced an increase during the lockdown period (18.9% vs. 26.7%; p = 0.026). Moreover, the proportion of severe cases decreased, as measured by an injury severity score (ISS) > 15 (37.3% vs. 26.8%; p = 0.014); while there were no differences in the median hospital length of stay and the mortality rate between the comparison groups. Finally, the decrease in overall admissions registered during the lockdown accounts for a 59% (IRR 0.41; 95% CI 0.31-0.54) change compared to the pre-lockdown period, when controlling for sex, age, mechanism of injury, and ISS. Conclusions Following periods of social isolation and curfews, trauma centers can expect drastic reductions in their overall patient volume with associated changes in trauma patterns. Our findings will help inform new interventions and improve healthcare preparedness for future or similar circumstances.